Effect of biogeographic history on population vulnerability in European amphibians. Issue 4 (31st March 2015) - Dufresnes, Christophe; Perrin, Nicolas
Abstract The genetic diversity of populations, which contributes greatly to their adaptive potential, is negatively affected by anthropogenic habitat fragmentation and destruction. However, continental‐scale losses of genetic diversity also resulted from the population expansions that followed the end of the last glaciation, an element that is rarely considered in a conservation context. We addressed this issue in a meta‐analysis in which we compared the spatial patterns of vulnerability of 18 widespread European amphibians in light of phylogeographic histories (glacial refugia and postglacial routes) and anthropogenic disturbances. Conservation statuses significantly worsened with distances from refugia, particularly in the context of industrial agriculture; human population density also had a negative effect. These findings suggest that features associated with the loss of genetic diversity in post‐glacial amphibian populations (such as enhanced fixation load or depressed adaptive potential) may increase their susceptibility to current threats (e.g., habitat fragmentation and pesticide use). We propose that the phylogeographic status of populations (i.e., refugial vs. post‐glacial) should be considered in conservation assessments for regional and national red lists.